ALIH KODE DALAM INTERAKSI SOSIAL PELAKU UMKM DI PELABUHAN TIMUR KAMAL KABUPATEN BANGKALAN - Sandy, Dea Kurnia (Universitas Sebelas Maret, 2023)
The development of UMKM business is currently high rapid. The reason is becausebusiness is promising and becomes the basis for earning income. On Madura Island, peoplecan be found running this business. In business, of course there is interaction between sellersand buyers. They use language as a communication tool in interaction. Madura Island has alocal language or mother tongue which can be called Madurese. This research focuses on codeswitching used in the social interactions of UMKM actors with their consumers. The methodused in this case is descriptive qualitative. The researcher uses code switching theory designedby Rahardi (2001). According to Rahardi (2001), code switching are divided into two, thereare internal code switching and external code switching. The method used in this research is aqualitative descriptive method. Data collection techniques through direct observation and writethe utterances in conversations that carried out during the interaction. The source data is takenfrom the observation location that name Pelabuhan Timur Kamal Kabupaten Bangkalan. Thedata taken is in the form of utterances between the sellers and the buyers, then transcript inwritten form. The findings of this research show that the code switching occurs in the socialinteractions of sellers with their consumers is internal code switching. There occurs codeswitching from Indonesian into Madurese or vice versa. Sellers respond the utterances ininteractions according to the language used by buyers. There are 14 internal’s code switchingthat found by the researcher from the social interaction between some UMKM actors with theirconsumers in Pelabuhan Timur Kamal Kabupaten Bangkalan.